2020
DOI: 10.26803/ijlter.19.4.12
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Differences Caused by Cognitive Variables on LET Performance: An Embedded Mixed Method Study

Abstract: The purpose of this study is to probe the differences caused by selected cognitive variables such as entrance test scores (ETS) and grade point average (GPA) on the performance of the graduates in the Licensure Examination for Teachers (LET). It entailed a causalcomparative embedded mixed method research design. The study followed a cohort of 42 purposively sampled graduates of Bachelor of Elementary Education (BEEd), College of Education (CoEd), Mindanao State University (MSU), General Santos City (GSC). Desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Studies on the predictors of teachers' licensure examination results in the Philippines were synthesized by Orlanda-Ventayen (2020). From the synthesis of the results of related articles, the variables arising as significant predictors were administrative, faculty, and student factors, attendance to review classes, and academic performance (Aquino & Balilla, 2015;Ferrer, Buted, & Ferrer;2015;Nool & Ladia, 2017;Quiambao, Baking, Buenviaje, Nuqui, & Cruz, 2015;Visco, 2015) Licensure examination performance was also linked with college academic performance of elementary education majors (Chan-Rabanal, 2016), and of both elementary and secondary education majors (Bellen, Abela, & Truya, 2018;Cahapay, 2020;Fontejon-Bonior & Dela Rama, 2018;Quiambao et al, 2015).…”
Section: Admission Variables As Predictors Of Teachers' Licensure Examination Ratingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the predictors of teachers' licensure examination results in the Philippines were synthesized by Orlanda-Ventayen (2020). From the synthesis of the results of related articles, the variables arising as significant predictors were administrative, faculty, and student factors, attendance to review classes, and academic performance (Aquino & Balilla, 2015;Ferrer, Buted, & Ferrer;2015;Nool & Ladia, 2017;Quiambao, Baking, Buenviaje, Nuqui, & Cruz, 2015;Visco, 2015) Licensure examination performance was also linked with college academic performance of elementary education majors (Chan-Rabanal, 2016), and of both elementary and secondary education majors (Bellen, Abela, & Truya, 2018;Cahapay, 2020;Fontejon-Bonior & Dela Rama, 2018;Quiambao et al, 2015).…”
Section: Admission Variables As Predictors Of Teachers' Licensure Examination Ratingsmentioning
confidence: 99%
“…Of these studies, admission test scores, IQ scores, and HSGPA showed varying levels of associations with LET ratings. For instance, admission test scores were reported to cause significant differences in the graduates' licensure performance (Cahapay, 2020), or emerge as significant predictors of ratings in the same examination (Ferrer et al, 2015;Gerundo & Balagtas, 2014;Labastilla, 2017).…”
Section: Admission Variables As Predictors Of Teachers' Licensure Examination Ratingsmentioning
confidence: 99%
“…There needs to be done other initiatives on the part of the students to prepare themselves prior to the actual licensure examinations. Literatures provided some predictors of passing the licensure examination for teachers such as academic achievement [17], attending LET review [18], mental ability [19], language proficiency [20], and field study course and internship [21], while on the part of the institution, studies suggest that teacher's personal and professional attribute [6], college admission test [22], metacognitive strategies [23] assessment procedures [24], and curriculum [25] are predictors of passing the LET.…”
Section: Pre-let and Let Performances Of Education Graduatesmentioning
confidence: 99%
“…Various factors affecting licensure examination performance have to be considered such as college admission test (Balagtas & Gerundio, 2014;Bansiong, 2019;Cahapay, 2020;Callena et al, 2019;Dagdag et al, 2017;Pascua & Navalta, 2011;Ruben, 2014;Solis-Foronda, 2017), general scholastic aptitude (Bansiong, 2019), college grade point average (Amanonce & Maramag, 2020;Bansiong, 2019;Cahapay, 2020;Chan-Rabanal, 2016;Dagdag et al, 2017;Esmeralda & Perez-Espinosa, 2015;Ferrer et al, 2015;Kalaw, 2017;Pascua & Navalta, 2011;Solis-Foronda, 2017), mock board examination and competency summative test (Bansiong, 2019), teaching aptitude test (Visco, 2015), retention examination (Balanquit et al, 2018;Corpuz, et al, 2017), English proficiency (Kalaw, 2017;Pascua & Navalta, 2011), educational attainment, teaching experience and competence of faculty members Quiambao, 2015;Ruben, 2014), LET review classes (Albite, 2019;Aquino & Balilla, 2015;Ferrer et al, 2015;Mendoza, 2014;Tan, 2016;Visco, 2015), accreditation status (Galenzoga, 2016;Gutierrez, 2016;Rosales et al, 2014), and library facilities (Quiambao et al, 2015).…”
Section: Implications To Teacher Trainingmentioning
confidence: 99%